Selenium-doped sulfide solid electrolyte and preparation method and application thereof
By introducing selenium elements and metal M cations into the sulfide solid electrolyte, a selenium-doped sulfide solid electrolyte with excellent performance was prepared, which solved the shortcomings of the existing sulfide solid electrolyte in air, solvent and lithium stability, and achieved a high-performance all-solid lithium secondary battery.
Patent Information
- Application Number
- CN202510237452.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-03-03
AI Technical Summary
The existing sulfide solid electrolytes have insufficient air, solvent and lithium stability, resulting in safety hazards and cycle stability problems in their applications.
The sulfide solid electrolyte doped with selenium is Li6±iP1-xMxS5-ySeyX. By introducing selenium elements and metal M cations, the stability of its air, solvent and lithium is improved, and a sulfide solid electrolyte with excellent performance is prepared by high-temperature calcination treatment.
The high ionic conductivity, excellent air, solvent and lithium stability of the sulfide solid electrolyte are achieved, and the all-solid lithium secondary battery produced exhibits excellent cycle stability.
Smart Images

Figure CN119725705A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid electrolytes and relates to a selenium-doped sulfide solid electrolyte and a preparation method and application thereof. Background Art
[0002] As a highly efficient secondary energy storage device, lithium-ion batteries have the advantages of high specific power, low self-discharge, and no memory effect. They have been widely used in many fields such as mobile communications, rail transportation, and aerospace. The use of flammable electrolytes in commercial lithium-ion batteries currently also poses a great safety hazard to lithium-ion batteries. Especially when abnormal operating conditions such as short circuit, overcharge, and collision occur, the temperature inside the battery will rise sharply, which will lead to safety problems such as thermal runaway, fire, and explosion, seriously threatening people’s lives and property safety. Therefore, high energy density and high safety are the current problems that lithium-ion batteries need to solve, and the research and development of battery systems with better performance is imminent.
[0003] All-solid-state lithium metal batteries have been considered as one of the most ideal next-generation energy storage devices due to their obvious advantages in safety and energy density. As a key component of all-solid-state lithium metal batteries, solid electrolytes have attracted widespread attention due to their higher thermal stability and better safety than liquid electrolytes. So far, a variety of solid electrolytes have been developed for the preparation of materials, including sulfides, oxides, and polymer electrolytes. Sulfide solid electrolytes stand out due to their excellent ionic conductivity and good formability.
[0004] However, the application of sulfide solid electrolytes still faces the following challenges: (1) Poor air stability and solvent stability. According to the “soft and hard acid-base” theory, PS4 3- The structural center P is a hard acid. Compared with the soft acid S, it is more likely to react with the hard acid O in a humid environment, attacking the weak PS bond to produce toxic H2S gas, which poses a potential threat to the environment and operators. (2) Poor stability to lithium. Since the sulfide solid electrolyte is thermodynamically unstable to metallic lithium, it is easy to cause uneven lithium ion deposition during the battery cycle and form lithium dendrites on the interface. When the lithium dendrites grow to a certain extent, they may pierce the solid electrolyte diaphragm, causing the battery to open or short-circuit and fail. Even if the lithium dendrites do not completely pierce the diaphragm, they may affect the battery's cycle stability due to factors such as local resistance changes, greatly shortening the battery's service life.
[0005] In order to meet the requirements of all-solid-state lithium battery applications, it is of great significance to develop a sulfide solid electrolyte with good air stability, solvent stability, electrochemical stability and high room temperature ionic conductivity to achieve high-performance batteries. Summary of the invention
[0006] The present invention aims at the deficiencies of sulfide solid electrolytes in the prior art and provides a selenium-doped sulfide solid electrolyte and a preparation method and application thereof. The selenium-doped sulfide solid electrolyte has excellent stability to air, organic solvents and lithium while ensuring high ionic conductivity, and the assembled all-solid-state battery exhibits excellent cycle stability.
[0007] The first object of the present invention is achieved by the following technical solutions: A selenium-doped sulfide solid electrolyte, the general chemical formula of which is Li 6±i P 1-x M x S 5-y Se y X, wherein 0≤i<1, 0<x<1, 0<y<1, M is one or more of Zr, Ta, Nb, Mo, Bi, In, Y, and X is one or more of Cl, Br, and F. This is a sulfide solid electrolyte of argyrodite phase.
[0008] Preferably, 0≤i≤0.8; more preferably, 0≤i≤0.5. i can be any value of 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, etc.
[0009] Preferably, 0.01≤x≤0.8, more preferably, 0.01≤x≤0.5. x can be any value of 0.01, 0.02, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, etc.
[0010] Preferably, 0.01≤y≤0.8, more preferably, 0.01≤y≤0.5. y can be any value of 0.01, 0.02, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, etc.
[0011] Preferably, 0≤i≤0.8, 0.01≤x≤0.8, 0.01≤y≤0.8.
[0012] Preferably, 0≤i≤0.5, 0.01≤x≤0.5, 0.01≤y≤0.5.
[0013] Preferably, M is one or more of Zr and Nb.
[0014] Preferably, M is Nb. When M is Nb, the obtained sulfide electrolyte has high room temperature ionic conductivity and better stability to air, organic solvents and lithium.
[0015] Preferably, X is Cl.
[0016] Preferably, the room temperature ionic conductivity of the sulfide solid electrolyte is 3×10 -3 ~5×10 -2 S / cm. More preferably, 3×10 -3 ~1×10 -2 S / cm, and further preferably 3×10 -3 ~8×10 -3 S / cm.
[0017] Preferably, after the sulfide solid electrolyte is exposed to a dry room dew point temperature of -40°C for 60 minutes, the room temperature ionic conductivity retention rate is ≥85%, and more preferably ≥87%.
[0018] Preferably, after the sulfide solid electrolyte is immersed in a benzene organic solvent, an ester organic solvent, an ether organic solvent, acetonitrile or tetrahydrofuran for 30 minutes, the room temperature ionic conductivity retention rate is ≥80%, and more preferably ≥83%.
[0019] Preferably, metallic lithium is used as a symmetrical electrode and the sulfide solid electrolyte is used as an electrolyte layer to assemble into a symmetrical battery. The symmetrical battery is cycle tested using a Blue Power CT2001A battery test system. The battery is measured at a current density of 0.1 mA cm -2 The lower stable cycle is ≥ 4000 hours, and more preferably ≥ 5000 hours.
[0020] The second object of the present invention is achieved by the following technical solutions: A method for preparing a selenium-doped sulfide solid electrolyte comprises the following steps: (1) According to the general formula Li 6±i P 1-x M x S 5-y Se y X, weigh Li2S, P2S5, LiX, selenium source and metal M source in stoichiometric ratios respectively and physically mix them to obtain precursor powder; (2) The precursor powder is calcined and naturally cooled to room temperature to obtain a selenium-doped argyrodite-phase sulfide solid electrolyte.
[0021] Preferably, the LiX is one or more of LiCl, LiBr and LiF.
[0022] Preferably, the selenium source and metal M source are Se powder, P powder and M a A b, wherein M is one or more of Zr, Ta, Nb, Mo, Bi, In, and Y, A is one or more of S, Cl, Br, and F, a=1-2, and b=2-5. More preferably, M a A b It is one or more of ZrS2, ZrCl4, TaCl5, TaS2, NbCl5, NbS2, MoCl5, MoS2, Bi2S5, BiCl3, In2S3, and YCl3. When Se is added in the form of a single substance, P powder needs to be added to undergo oxidation-reduction with Se to promote the reaction. When P powder is not added, Se cannot be effectively doped.
[0023] Preferably, the selenium source and the metal M source are M c Se d , wherein M is one or more of Zr, Ta, Nb, Mo, Bi, In, and Y, c=1-2, d=2-5. More preferably, M c Se d It is one or more of ZrSe2, Ta2Se5, Nb2Se5, Mo2Se5, Bi2Se5, In2Se3, and Y2Se3.
[0024] Preferably, the physical mixing is mechanical mixing, including high-energy ball milling, mechanical stirring, mechanical shaking, grinding or roller milling, and the mixing time is 20 minutes to 48 hours.
[0025] Preferably, the calcination treatment is carried out in an inert atmosphere, the heating rate is 1-5°C / min, the calcination temperature is 500-600°C, and the calcination time is 0.5-24 hours.
[0026] The third object of the present invention is achieved by the following technical solutions: An all-solid-state lithium secondary battery comprises a positive electrode, a negative electrode and the above-mentioned selenium-doped argyrodite phase sulfide solid electrolyte.
[0027] Compared with the prior art, the present invention has the following beneficial effects: 1. Use elements with larger radius and lower electronegativity than S element to replace S element to improve air stability and solvent stability. However, the ionic radius of the S-substituted element must be controlled within a certain range, otherwise it will be difficult to enter PS4. 3-Tetrahedron exists in the lattice in a free form, resulting in the generation of byproducts and reducing structural stability. After research, it was found that the present invention can produce excellent effects by introducing selenium with a larger ionic radius (~103 pm) and a lower electronegativity (2.55) to replace sulfur with a smaller ionic radius (~88 pm) and a higher electronegativity (2.58), which is specifically manifested as: selenium replacing sulfur can increase the unit cell volume, broaden the transmission channel of ions inside the lithium electrolyte, thereby increasing Li + The ion transfer rate makes the prepared sulfide solid electrolyte have high ion conductivity. The replacement of sulfur by selenium weakens the Coulomb attraction in the lattice, forming a more stable crystal structure and improving the chemical stability of the sulfide solid electrolyte - air stability and solvent stability.
[0028] 2. The metal M cation introduced in the present invention can form Li + Alloys with low diffusion energy barriers and metal alloys can promote the uniform deposition of lithium metal at the interface, thereby preventing the growth of lithium dendrites and improving lithium stability.
[0029] 3. The present invention adopts Se to replace S element and introduces metal M cation to prepare a new selenium-doped argyrodite phase sulfide solid electrolyte. After being exposed to a dry room dew point temperature of -40°C for 60 minutes, the room temperature ionic conductivity retention rate reaches more than 85%, indicating that it has excellent air stability; after being immersed in benzene, ester, ether, acetonitrile, and tetrahydrofuran organic solutions for 30 minutes, the room temperature ionic conductivity retention rate reaches more than 80%, indicating that it has excellent solvent stabilizer; the sulfide solid electrolyte is used to attach lithium sheets on both sides to prepare a lithium battery, and the current density is 0.1 mA cm -2 It can be stably cycled for more than 4000 hours under high temperature, indicating that it has excellent stability to lithium.
[0030] 4. Since the sulfide solid electrolyte of the present invention has high air stability, solvent stability and electrochemical stability, the all-solid-state lithium secondary battery prepared using the sulfide solid electrolyte has good long-cycle stability and exhibits excellent cycle stability.
[0031] 5. When Se replaces S element and Nb element is introduced, the prepared argyrodite phase sulfide solid electrolyte has better air stability, solvent stability and electrochemical stability, and the all-solid-state lithium secondary battery prepared therefrom has better cycle stability.
[0032] 6. The preparation method of the sulfide solid electrolyte of the present invention is simple to operate. According to the general formula, Li2S, P2S5, LiX, selenium source and metal M source in stoichiometric ratio are weighed and physically mixed to obtain a precursor powder. After further high-temperature calcination, the product can be obtained by naturally cooling to room temperature. It is highly practical and convenient for large-scale production.
[0033] 7. In the preparation process of the sulfide solid electrolyte of the present invention, when Se is added in the form of a single substance, P powder is creatively added to react with Se to undergo oxidation-reduction reaction to promote the reaction. The selenium source and metal M source are Se powder, P powder and M a A b The performance of the sulfide solid electrolyte prepared when the selenium source is M c Se d . BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Li6P in Example 6 of the present invention 0.95 Nb 0.05 S 4.9 Se 0.1 AC impedance spectra of the Cl sulfide solid electrolyte and the Li6PS5Cl sulfide solid electrolyte in Comparative Example 1; Figure 2 Li6P in Example 6 of the present invention 0.95 Nb 0.05 S 4.9 Se 0.1 The lithium / / lithium symmetric battery cycle curves of the Cl sulfide solid electrolyte and the Li6PS5Cl sulfide solid electrolyte in Comparative Example 1; Figure 3 Li6P in Example 6 of the present invention 0.95 Nb 0.05 S 4.9 Se 0.1 Long cycle diagram of all-solid-state batteries at 1C rate using Li6PS5Cl sulfide solid electrolyte and Li6PS5Cl sulfide solid electrolyte in Comparative Example 1. DETAILED DESCRIPTION
[0035] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosure of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0036] In the following examples and comparative examples, the room temperature is approximately 25°C.
[0037] Example 1
[0038] The sulfide solid electrolyte of this embodiment is prepared by the following method: Li2S, P2S5, LiCl, In2S3, Se and P with purity of more than 99% were weighed in an agate mortar according to the stoichiometric ratio under an argon atmosphere, and grinded for 30 minutes under the condition of water content less than 10 ppm to obtain Li 6.1 P 0.95 In 0.05 S 4.9 Se 0.1 Cl precursor powder; The precursor powder was sintered in a muffle furnace at 550 °C for 4 hours at a heating rate of 4 °C / min under an inert atmosphere (argon), and then naturally cooled to room temperature and ground to obtain Li 6.1 P 0.95 In 0.05 S 4.9 Se 0.1 Cl sulfide solid electrolyte.
[0039] Performance testing and battery assembly The ground Li 6.1 P 0.95 In 0.05 S 4.9 Se 0.1 The Cl sulfide solid electrolyte powder was pressed into a tablet and its room temperature ionic conductivity was tested to be 4.3×10 -3 S cm -1 Compared with the Li6PS5Cl sulfide solid electrolyte in Comparative Example 1, the ionic conductivity is increased by 48.3%; after being exposed to the dew point temperature of the air in the dry room (dry room dew point temperature) at -60℃, -50℃, and -40℃ for 60 minutes, the room temperature conductivity is 4.1×10 -3 S cm -1 4.01×10 -3 S cm -1 , 3.9×10 -3 S cm -1 , the retention rates were 95.3%, 93.3% and 90.7% respectively; Li 6.1 P 0.95 In 0.05 S 4.9 Se 0.1 After the Cl sulfide solid electrolyte was immersed in toluene, butyl butyrate, ether, acetonitrile, and tetrahydrofuran for 30 min, the room temperature ionic conductivity was 3.7×10-3 S cm -1 , 3.71×10 -3 S cm -1 ,3.66×10 -3 S cm -1 , 3.62×10 -3 S cm -1 , 3.64×10 -3 S cm -1 The retention rates were 86%, 86.3%, 85.1%, 84.2% and 84.7% respectively.
[0040] With lithium metal as the symmetrical electrode, Li 6.1 P 0.95 In 0.05 S 4.9 Se 0.1 The Cl sulfide solid electrolyte was used as the electrolyte layer and assembled into a symmetrical battery. The battery was cycled using a Blue Power CT2001A battery test system. The battery was tested at a current density of 0.1 mAcm -2 It can stably cycle for 5100 hours.
[0041] Li 6.1 P 0.95 In 0.05 S 4.9 Se 0.1 Cl sulfide solid electrolyte, LiCoO2 positive electrode and metal lithium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 3.0~4.2 V, the rate is 1C, and the constant rate charge and discharge is performed. After 300 cycles, the capacity retention rate is 87.1%.
[0042] Example 2
[0043] The sulfide solid electrolyte of this embodiment is prepared by the following method: Li2S, P2S5, LiCl, YCl3, Se and P with a purity of more than 99% were weighed in an agate mortar according to the stoichiometric ratio under an argon atmosphere, and grinded for 30 minutes under the condition of less than 10 ppm of water to obtain Li 6.1 P 0.95 Y 0.05 S 4.9 Se 0.1 Cl precursor powder; The precursor powder was sintered in a muffle furnace at 550 °C for 4 hours at a heating rate of 4 °C / min under an inert atmosphere (argon), and then naturally cooled to room temperature and ground to obtain Li 6.1 P 0.95 Y0.05 S 4.9 Se 0.1 Cl sulfide solid electrolyte.
[0044] Performance testing and battery assembly The ground Li 6.1 P 0.95 Y 0.05 S 4.9 Se 0.1 The Cl sulfide solid electrolyte powder was pressed into tablets, and its room temperature ionic conductivity was tested to be 3.76×10 -3 S cm -1 Compared with the Li6PS5Cl sulfide solid electrolyte in Comparative Example 1, the ionic conductivity is increased by 29.7%; after being exposed to the dry room dew point temperature of -60℃, -50℃, and -40℃ for 60min, the room temperature conductivity is 3.51×10 -3 S cm -1 ,3.41×10 -3 S cm -1 , 3.29×10 -3 S cm -1 , the retention rates were 93.4%, 90.7% and 87.5% respectively; 6.1 P 0.95 Y 0.05 S 4.9 Se 0.1 After the Cl sulfide solid electrolyte was immersed in toluene, butyl butyrate, ether, acetonitrile, and tetrahydrofuran for 30 min, the room temperature ionic conductivity was 3.2×10 -3 S cm -1 , 3.15×10 -3 S cm -1 ,3.16×10 -3 S cm -1 , 3.12×10 -3 S cm -1 , 3.14×10 -3 S cm -1 The retention rates were 85.1%, 83.8%, 84%, 83% and 83.5% respectively.
[0045] With lithium metal as the symmetrical electrode, Li 6.1 P 0.95 Y 0.05 S 4.9 Se 0.1 The Cl sulfide solid electrolyte was used as the electrolyte layer and assembled into a symmetrical battery. The battery was cycled using a Blue Power CT2001A battery test system. The battery was tested at a current density of 0.1 mAcm -2 It can stably cycle for 7800 hours.
[0046] Li 6.1 P 0.95 Y 0.05 S 4.9 Se 0.1 Cl sulfide solid electrolyte, LiCoO2 positive electrode and metal lithium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 3.0~4.2 V, the rate is 1C, and the constant rate charge and discharge is performed. After 300 cycles, the capacity retention rate is 83.5%.
[0047] Example 3
[0048] The sulfide solid electrolyte of this embodiment is prepared by the following method: Li2S, P2S5, LiCl, ZrS2, Se and P with purity of more than 99% were weighed in an agate mortar according to the stoichiometric ratio under an argon atmosphere, and grinded for 30 minutes under the condition of water content less than 10 ppm to obtain Li 6.05 P 0.95 Zr 0.05 S 4.9 Se 0.1 Cl precursor powder; The precursor powder was sintered in a muffle furnace at 550 °C for 4 hours at a heating rate of 4 °C / min under an inert atmosphere (argon), and then naturally cooled to room temperature and ground to obtain Li 6.05 P 0.95 Zr 0.05 S 4.9 Se 0.1 Cl sulfide solid electrolyte; Performance testing and battery assembly The ground Li 6.05 P 0.95 Zr 0.05 S 4.9 Se 0.1 The Cl sulfide solid electrolyte powder was pressed into a tablet and its room temperature ionic conductivity was tested to be 3.91×10 -3 S cm -1 Compared with the Li6PS5Cl sulfide solid electrolyte in Comparative Example 1, the ionic conductivity is increased by 34.8%; after being exposed to the dry room dew point temperature of -60℃, -50℃, and -40℃ for 60min, the room temperature conductivity is 3.72×10 -3 S cm -1 , 3.65×10 -3 S cm -1 , 3.57×10 -3 S cm -1The retention rates were 95.1%, 93.4% and 91.3% respectively. After the sulfide solid electrolyte was immersed in toluene, butyl butyrate, ether, acetonitrile and tetrahydrofuran for 30 min, the room temperature ionic conductivity was 3.42×10 -3 S cm -1 , 3.44×10 -3 S cm -1 , 3.36×10 -3 S cm -1 , 3.37×10 -3 Scm -1 ,3.39×10 -3 S cm -1 The retention rates were 87.5%, 88%, 85.9%, 86.2% and 86.7% respectively.
[0049] With lithium metal as the symmetrical electrode, Li 6.05 P 0.95 Zr 0.05 S 4.9 Se 0.1 The Cl sulfide solid electrolyte was used as the electrolyte layer and assembled into a symmetrical battery. The battery was cycled using a Blue Power CT2001A battery test system. The battery was tested at a current density of 0.1 mAcm -2 It can stably cycle for 7300 hours; Li 6.05 P 0.95 Zr 0.05 S 4.9 Se 0.1 Cl sulfide solid electrolyte, LiCoO2 positive electrode and metal lithium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using a Blue Power CT2001A battery test system. The charge and discharge voltage range is 3.0~4.2 V, the rate is 1C, and constant rate charge and discharge are performed. After 300 cycles, the capacity retention rate is 91.2%.
[0050] Example 4
[0051] The sulfide solid electrolyte of this embodiment is prepared by the following method: Li2S, P2S5, LiCl, TaCl5, Se and P with purity of more than 99% were weighed in an agate mortar according to the stoichiometric ratio under an argon atmosphere, and grinded for 30 minutes under the condition of less than 10 ppm of water to obtain Li6P 0.95 Ta 0.05 S 4.9 Se 0.1 Cl precursor powder; The precursor powder was sintered in a muffle furnace at 550 °C for 4 hours at a heating rate of 4 °C / min under an inert atmosphere (argon), and then naturally cooled to room temperature and ground to obtain Li6P 0.95 Ta 0.05 S 4.9 Se 0.1 Cl sulfide solid electrolyte; Performance testing and battery assembly The ground Li6P 0.95 Ta 0.05 S 4.9 Se 0.1 The Cl sulfide solid electrolyte powder was pressed into a tablet and its room temperature ionic conductivity was tested to be 4.23×10 -3 S cm -1 Compared with the Li6PS5Cl sulfide solid electrolyte in Comparative Example 1, the ionic conductivity is increased by 45.9%; after being exposed to the dry room dew point temperature of -60℃, -50℃, and -40℃ for 60min, the room temperature conductivity is 3.95×10 -3 S cm -1 , 3.87×10 -3 S cm -1 ,3.82×10 -3 S cm -1 The retention rates were 93.4%, 91.5% and 90.3% respectively. After the sulfide solid electrolyte was immersed in toluene, butyl butyrate, ether, acetonitrile and tetrahydrofuran for 30 min, the room temperature ionic conductivity was 3.69×10 -3 S cm -1 , 3.68×10 -3 S cm -1 ,3.72×10 -3 S cm -1 , 3.6×10 -3 S cm -1 ,3.58×10 -3 S cm -1 The retention rates were 87.2%, 87%, 87.9%, 85.1% and 84.6% respectively.
[0052] With lithium metal as the symmetrical electrode, Li6P 0.95 Ta 0.05 S 4.9 Se 0.1 The Cl sulfide solid electrolyte was used as the electrolyte layer and assembled into a symmetrical battery. The battery was cycled using a Blue Power CT2001A battery test system. The battery was tested at a current density of 0.1 mAcm -2 It can stably cycle for 6800 hours.
[0053] Li6P 0.95 Ta 0.05 S 4.9 Se 0.1 Cl sulfide solid electrolyte, LiCoO2 positive electrode and metal lithium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 3.0~4.2 V, the rate is 1C, and the constant rate charge and discharge is performed. After 300 cycles, the capacity retention rate is 88.1%.
[0054] Example 5
[0055] The sulfide solid electrolyte of this embodiment is prepared by the following method: Li2S, P2S5, LiCl, and Nb2Se5 with a purity of more than 99% were weighed in an argon atmosphere according to the stoichiometric ratio and placed in an agate mortar. Li6P was obtained after grinding for 30 minutes under the condition of a water content of less than 10 ppm. 0.95 Nb 0.05 S 4.9 Se 0.1 Cl precursor powder; The precursor powder was sintered in a muffle furnace at 550 °C for 4 hours at a heating rate of 4 °C / min under an inert atmosphere (argon), and then naturally cooled to room temperature and ground to obtain Li6P 0.95 Nb 0.05 S 4.9 Se 0.1 Cl sulfide solid electrolyte.
[0056] Performance testing and battery assembly The ground Li6P 0.95 Nb 0.05 S 4.9 Se 0.1 The Cl sulfide solid electrolyte powder was pressed into a tablet and its room temperature ionic conductivity was tested to be 5.26×10 -3 S cm -1 After being exposed to the dew point temperature of -60℃, -50℃ and -40℃ in the dry room for 60min, the room temperature conductivity was 5.03×10 -3 S cm -1 ,4.91×10 -3 S cm -1 4.82×10 -3 S cm -1 The retention rates were 95.6%, 93.3% and 91.6% respectively. After the sulfide solid electrolyte was immersed in toluene, butyl butyrate, ether, acetonitrile and tetrahydrofuran for 30 min, the room temperature ionic conductivity was 4.64×10-3 S cm -1 4.65×10 -3 S cm -1 4.68×10 -3 S cm -1 4.69×10 -3 S cm -1 ,4.58×10 -3 S cm -1 The retention rates were 88.2%, 88.4%, 88.9%, 89.1% and 87.1% respectively.
[0057] With lithium metal as the symmetrical electrode, Li6P 0.95 Nb 0.05 S 4.9 Se 0.1 The Cl sulfide solid electrolyte was used as the electrolyte layer and assembled into a symmetrical battery. The battery was cycled using a Blue Power CT2001A battery test system. The battery was tested at a current density of 0.1 mAcm -2 It can stably cycle for 8100 hours.
[0058] Li6P 0.95 Nb 0.05 S 4.9 Se 0.1 Cl sulfide solid electrolyte, LiCoO2 positive electrode and metal lithium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 3.0~4.2 V, the rate is 1C, and the constant rate charge and discharge is performed. After 300 cycles, the capacity retention rate is 91.5%.
[0059] Example 6
[0060] The sulfide solid electrolyte of this embodiment is prepared by the following method: Li2S, P2S5, LiCl, NbCl5, Se and P with purity of more than 99% were weighed in an agate mortar according to the stoichiometric ratio under an argon atmosphere, and grinded for 30 minutes under the condition of less than 10 ppm of water to obtain Li6P 0.95 Nb 0.05 S 4.9 Se 0.1 Cl precursor powder; The precursor powder was sintered in a muffle furnace at 550 °C for 4 hours at a heating rate of 4 °C / min under an inert atmosphere (argon), and then naturally cooled to room temperature and ground to obtain Li6P 0.95 Nb 0.05 S 4.9 Se 0.1Cl sulfide solid electrolyte.
[0061] Performance testing and battery assembly The ground Li6P 0.95 Nb 0.05 S 4.9 Se 0.1 The Cl sulfide solid electrolyte powder was pressed into tablets, and its room temperature ionic conductivity was tested to be 5.38×10 -3 S cm -1 Compared with the Li6PS5Cl sulfide solid electrolyte in Comparative Example 1, the ionic conductivity of the electrolyte increased by 85.5%; after exposure to the dry room dew point temperature of -60℃, -50℃, and -40℃ for 60min, the room temperature conductivity was 5.16×10 -3 S cm -1 , 5.04×10 -3 S cm -1 4.95×10 -3 S cm -1 The retention rates were 95.9%, 93.7% and 92.0% respectively. After the sulfide solid electrolyte was immersed in toluene, butyl butyrate, ether, acetonitrile and tetrahydrofuran for 30 min, the room temperature ionic conductivity was 4.8×10 -3 S cm -1 4.83×10 -3 S cm -1 ,4.86×10 -3 S cm -1 4.82×10 -3 S cm -1 4.89×10 -3 S cm -1 The retention rates were 89.2%, 89.8%, 90.3%, 89.6% and 90.9% respectively; the conductivity after exposure at -40°C and immersion in acetonitrile solution was compared with the ionic conductivity of the Li6PS5Cl sulfide solid electrolyte in Comparative Example 1. Figure 1 shown.
[0062] With lithium metal as the symmetrical electrode, Li6P 0.95 Nb 0.05 S 4.9 Se 0.1 The Cl sulfide solid electrolyte was used as the electrolyte layer and assembled into a symmetrical battery. The battery was cycled using a Blue Power CT2001A battery test system. The battery was tested at a current density of 0.1 mAcm -2 It can be stably cycled for 8300 hours under the same conditions, showing excellent stability to lithium compared with the Li6PS5Cl sulfide solid electrolyte in Comparative Example 1 (see Figure 2 ).
[0063] Li6P 0.95 Nb 0.05 S 4.9 Se 0.1 Cl sulfide solid electrolyte, LiCoO2 positive electrode and metal lithium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 3.0~4.2 V, the rate is 1C, and the constant rate charge and discharge is performed. After 300 cycles, the capacity retention rate is 92.4%. Figure 3 As shown, the capacity retention rate of the Li6PS5Cl sulfide solid electrolyte in Comparative Example 1 after 300 cycles at a rate of 1C is only 76.6%.
[0064] Example 7
[0065] The sulfide solid electrolyte of this embodiment is prepared by the following method: Li2S, P2S5, LiCl, MoCl5, Se and P with purity of more than 99% were weighed in an agate mortar according to the stoichiometric ratio under an argon atmosphere, and grinded for 30 minutes under the condition of water content less than 10 ppm to obtain Li6P 0.95 Mo 0.05 S 4.9 Se 0.1 Cl precursor powder; The precursor powder was sintered in a muffle furnace at 550 °C for 4 hours at a heating rate of 4 °C / min under an inert atmosphere (argon), and then naturally cooled to room temperature and ground to obtain Li6P 0.95 Mo 0.05 S 4.9 Se 0.1 Cl sulfide solid electrolyte.
[0066] Performance testing and battery assembly The ground Li6P 0.95 Mo 0.05 S 4.9 Se 0.1 The Cl sulfide solid electrolyte powder was pressed into a tablet and its room temperature ionic conductivity was tested to be 4.43×10 -3 S cm -1 Compared with the Li6PS5Cl sulfide solid electrolyte in Comparative Example 1, the ionic conductivity is increased by 52.8%; after being exposed to the dry room dew point temperature of -60℃, -50℃, and -40℃ for 60min, the room temperature conductivity is 4.2×10 -3 S cm -1 4.12×10 -3 S cm -14.05×10 -3 S cm -1 The retention rates were 94.8%, 93%, and 91.4%, respectively. After the sulfide solid electrolyte was immersed in toluene, butyl butyrate, ether, acetonitrile, and tetrahydrofuran for 30 min, the room temperature ionic conductivity was 3.99×10 -3 S cm -1 ,3.92×10 -3 S cm -1 , 3.96×10 -3 S cm -1 ,3.82×10 -3 S cm -1 ,3.86×10 -3 S cm -1 The retention rates were 90.1%, 88.5%, 89.4%, 86.2% and 87.1% respectively.
[0067] With lithium metal as the symmetrical electrode, Li6P 0.95 Mo 0.05 S 4.9 Se 0.1 The Cl sulfide solid electrolyte was used as the electrolyte layer and assembled into a symmetrical battery. The battery was cycled using a Blue Power CT2001A battery test system. The battery was tested at a current density of 0.1 mAcm -2 It can stably cycle for 6800 hours.
[0068] Li6P 0.95 Mo 0.05 S 4.9 Se 0.1 Cl sulfide solid electrolyte, LiCoO2 positive electrode and metal lithium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 3.0~4.2 V, the rate is 1C, and the constant rate charge and discharge is performed. After 300 cycles, the capacity retention rate is 85.4%.
[0069] Example 8 The sulfide solid electrolyte of this embodiment is prepared by the following method: Li2S, P2S5, LiCl, Bi2S5, Se and P with purity of more than 99% were weighed in an agate mortar according to the stoichiometric ratio under an argon atmosphere, and grinded for 30 minutes under the condition of less than 10 ppm of water to obtain Li6P 0.95 Bi 0.05 S 4.9 Se 0.1 Cl precursor powder; The precursor powder was sintered in a muffle furnace at 550 °C for 4 hours at a heating rate of 4 °C / min under an inert atmosphere (argon), and then naturally cooled to room temperature and ground to obtain Li6P 0.95 Bi 0.05 S 4.9 Se 0.1 Cl sulfide solid electrolyte.
[0070] Performance testing and battery assembly The ground Li6P 0.95 Bi 0.05 S 4.9 Se 0.1 The Cl sulfide solid electrolyte powder was pressed into tablets, and its room temperature ionic conductivity was tested to be 3.98×10 -3 S cm -1 Compared with the Li6PS5Cl sulfide solid electrolyte in Comparative Example 1, the ionic conductivity is increased by 37.2%; after being exposed to the dry room dew point temperature of -60℃, -50℃, and -40℃ for 60min, the room temperature conductivity is 3.8×10 -3 S cm -1 , 3.7×10 -3 S cm -1 , 3.62×10 -3 S cm -1 The retention rates were 95.5%, 93%, and 91%, respectively. After the sulfide solid electrolyte was immersed in toluene, butyl butyrate, ether, acetonitrile, and tetrahydrofuran for 30 min, the room temperature ionic conductivity was 3.5×10 -3 S cm -1 , 3.45×10 -3 S cm -1 ,3.46×10 -3 S cm -1 , 3.42×10 -3 S cm -1 ,3.46×10 -3 S cm -1 The retention rates were 87.9%, 86.7%, 86.9%, 85.9% and 86.9% respectively.
[0071] With lithium metal as the symmetrical electrode, Li6P 0.95 Bi 0.05 S 4.9 Se 0.1 The Cl sulfide solid electrolyte was used as the electrolyte layer and assembled into a symmetrical battery. The battery was cycled using a Blue Power CT2001A battery test system. The battery was tested at a current density of 0.1 mAcm -2 It can stably cycle for 5300 hours.
[0072] Li6P 0.95 Bi 0.05 S 4.9 Se 0.1 Cl sulfide solid electrolyte, LiCoO2 positive electrode and metal lithium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 3.0~4.2 V, the rate is 1C, and the constant rate charge and discharge is performed. After 300 cycles, the capacity retention rate is 85.1%.
[0073] Comparative Example 1 The sulfide solid electrolyte of Comparative Example 1 was prepared by the following method: Under argon atmosphere, Li2S, P2S5, and LiCl with a purity of more than 99% were weighed according to the stoichiometric ratio and placed in an agate mortar, and grinded for 30 minutes under the condition of a water content of less than 10 ppm to obtain Li6PS5Cl precursor powder; The precursor powder was sintered at 550 °C for 4 hours in a muffle furnace at a heating rate of 4 °C / min under an inert atmosphere (argon), and finally cooled to room temperature and ground evenly to obtain Li6PS5Cl sulfide solid electrolyte.
[0074] Performance testing and battery assembly The ground Li6PS5Cl sulfide solid electrolyte powder was pressed into a tablet and its room temperature ionic conductivity was tested to be 2.9×10 -3 S cm -1 After being exposed to the dew point temperature of -60℃, -50℃ and -40℃ in the dry room for 60min, the room temperature conductivity was 2.47×10 -3 S cm -1 , 2.39×10 -3 S cm -1 , 2.32×10 -3 S cm -1 , the ionic conductivity retention rates were 85.2%, 82.4%, and 80.1%, respectively; after the sulfide solid electrolyte was immersed in toluene, butyl butyrate, ether, acetonitrile, and tetrahydrofuran for 30 min, the room temperature ionic conductivity was 2.07×10 -3 S cm -1 , 2.02×10 -3 S cm -1 , 2.01×10 -3 S cm -1 , 2.05×10 -3 S cm -1 , 2×10 -3 S cm-1 , the retention rates were 71.4%, 69.7%, 69.3%, 70.7% and 69% respectively; The symmetrical battery was assembled with lithium metal as the symmetrical electrode and Li6PS5Cl sulfide solid electrolyte as the electrolyte layer. The battery was cycled using the Blue Power CT2001A battery test system. The battery was tested at a current density of 0.1 mA cm -2 It can cycle for 1700 hours.
[0075] The Li6PS5Cl sulfide solid electrolyte, LiCoO2 positive electrode and metal lithium negative electrode were assembled into an all-solid-state battery. The battery was tested for electrochemical performance using a Blue Power CT2001A battery test system. The charge and discharge voltage range was 3.0~4.2 V, the rate was 1C, and constant rate charge and discharge were performed. After 300 cycles, the capacity retention rate was 76.6%.
[0076] Comparative Example 2 The sulfide solid electrolyte of Comparative Example 2 was prepared by the following method: Li2S, P2S5, LiCl, and NbCl5 with a purity of more than 99% were weighed in an argon atmosphere according to the stoichiometric ratio and placed in an agate mortar. Li6P was obtained after grinding for 30 minutes under the condition of a water content of less than 10 ppm. 0.95 Nb 0.05 S5Cl precursor powder; The precursor powder was sintered in a muffle furnace at 550 °C for 4 hours at a heating rate of 4 °C / min under an inert atmosphere (argon), and then naturally cooled to room temperature and ground to obtain Li6P 0.95 Nb 0.05 S5Cl sulfide solid electrolyte.
[0077] Performance testing and battery assembly The ground Li6P 0.95 Nb 0.05 S5Cl sulfide solid electrolyte powder was pressed into tablets, and its room temperature ionic conductivity was tested to be 3.41×10 -3 S cm -1 ; After being exposed to the dew point temperature of -60℃, -50℃ and -40℃ in the dry room for 60min, the room temperature conductivity was 3.03×10 -3 S cm -1 , 2.93×10 -3 S cm -1 , 2.81×10 -3 S cm -1The retention rates were 88.9%, 85.6% and 82.4% respectively. After the sulfide solid electrolyte was immersed in toluene, butyl butyrate, ether, acetonitrile and tetrahydrofuran for 30 min, the room temperature ionic conductivity was 2.75×10 -3 S cm -1 , 2.76×10 -3 S cm -1 , 2.71×10 -3 S cm -1 , 2.7×10 -3 S cm -1 , 2.73×10 -3 S cm -1 The retention rates were 80.6%, 80.9%, 79.5%, 79.2% and 80.1% respectively.
[0078] With lithium metal as the symmetrical electrode, Li6P 0.95 Nb 0.05 The S5Cl sulfide solid electrolyte was used as the electrolyte layer. The battery was assembled into a symmetrical battery and cycled using a Blue Power CT2001A battery test system. The battery was tested at a current density of 0.1 mA cm -2 It can stably cycle for 3100 hours.
[0079] Li6P 0.95 Nb 0.05 S5Cl sulfide solid electrolyte, LiCoO2 positive electrode and metal lithium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 3.0~4.2 V, the rate is 1C, and the constant rate charge and discharge is performed. After 300 cycles, the capacity retention rate is 82.1%.
[0080] Comparative Example 3 The sulfide solid electrolyte of Comparative Example 3 was prepared by the following method: Li2S, P2S5, LiCl, Se and P with a purity of more than 99% were weighed in an agate mortar according to the stoichiometric ratio under an argon atmosphere, and Li6PS was obtained after grinding for 30 minutes under the condition of less than 10 ppm of water. 4.9 Se 0.1 Cl precursor powder; The precursor powder was sintered in a muffle furnace at 550 °C for 4 h at a heating rate of 4 °C / min under an inert atmosphere (argon), and then naturally cooled to room temperature and ground to obtain Li6PS 4.9 Se 0.1 Cl sulfide solid electrolyte.
[0081] Performance testing and battery assembly The ground Li6PS 4.9 Se 0.1 The Cl sulfide solid electrolyte powder was pressed into tablets, and its room temperature ionic conductivity was tested to be 3.32×10 -3 S cm -1 ; After being exposed to the dew point temperature of -60℃, -50℃ and -40℃ in the dry room for 60min, the room temperature conductivity was 3.01×10 -3 S cm -1 , 2.92×10 -3 S cm -1 , 2.83×10 -3 S cm -1 The retention rates were 90.7%, 88%, and 85.2%, respectively. After the sulfide solid electrolyte was immersed in toluene, butyl butyrate, ether, acetonitrile, and tetrahydrofuran for 30 minutes, the room temperature ionic conductivity was 2.73×10 -3 S cm -1 , 2.71×10 -3 S cm -1 , 2.74×10 -3 S cm -1 , 2.75×10 -3 S cm -1 , 2.73×10 -3 S cm -1 The retention rates were 82.2%, 81.6%, 82.5%, 82.8% and 82.2% respectively.
[0082] With lithium metal as the symmetrical electrode, Li6PS 4.9 Se 0.1 The Cl sulfide solid electrolyte was used as the electrolyte layer and assembled into a symmetrical battery. The battery was cycled using a Blue Power CT2001A battery test system at a current density of 0.1 mA cm -2 It can stably cycle for 3500 hours.
[0083] Li6PS 4.9 Se 0.1 Cl sulfide solid electrolyte, LiCoO2 positive electrode and metal lithium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 3.0~4.2 V, the rate is 1C, and the constant rate charge and discharge is performed. After 300 cycles, the capacity retention rate is 83.5%.
[0084] Comparative Example 4 The sulfide solid electrolyte of Comparative Example 4 was prepared by the following method: Li2S, P2S5, LiCl, NbCl5, Te and P with purity of more than 99% were weighed in an agate mortar according to the stoichiometric ratio under an argon atmosphere, and grinded for 30 minutes under the condition of water content less than 10 ppm to obtain Li6P 0.95 Nb 0.05 S 4.9 Te 0.1 Cl precursor powder; The precursor powder was sintered in a muffle furnace at 550 °C for 4 hours at a heating rate of 4 °C / min under an inert atmosphere (argon), and then naturally cooled to room temperature and ground to obtain Li6P 0.95 Nb 0.05 S 4.9 Te 0.1 Cl sulfide solid electrolyte.
[0085] Performance testing and battery assembly The ground Li6P 0.95 Nb 0.05 S 4.9 Te 0.1 The Cl sulfide solid electrolyte powder was pressed into a tablet and its room temperature ionic conductivity was tested to be 3.17×10 -3 S cm -1 ; After being exposed to the dry room dew point temperature of -60℃, -50℃, and -40℃ for 60min, the room temperature conductivity was 2.7×10 -3 S cm -1 , 2.59×10 -3 S cm -1 , 2.48×10 -3 S cm -1 The retention rates were 85.2%, 81.7% and 78.2% respectively. After the sulfide solid electrolyte was immersed in toluene, butyl butyrate, ether, acetonitrile and tetrahydrofuran for 30 min, the room temperature ionic conductivity was 2.3×10 -3 S cm -1 , 2.32×10 -3 S cm -1 , 2.29×10 -3 S cm -1 , 2.34×10 -3 S cm -1 , 2.28×10 -3 S cm -1 The retention rates were 72.6%, 73.2%, 72.2%, 73.8% and 71.9% respectively.
[0086] With lithium metal as the symmetrical electrode, Li6P 0.95 Nb0.05 S 4.9 Te 0.1 The Cl sulfide solid electrolyte was used as the electrolyte layer and assembled into a symmetrical battery. The battery was cycled using a Blue Power CT2001A battery test system. The battery was tested at a current density of 0.1 mAcm -2 It can stably cycle for 1600 hours.
[0087] Li6P 0.95 Nb 0.05 S 4.9 Te 0.1 Cl sulfide solid electrolyte, LiCoO2 positive electrode and metal lithium negative electrode are assembled into an all-solid-state battery. The battery is tested for electrochemical performance using the Blue Power CT2001A battery test system. The charge and discharge voltage range is 3.0~4.2 V, the rate is 1C, and the constant rate charge and discharge is performed. After 300 cycles, the capacity retention rate is 75.4%.
[0088] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0089] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.
[0090] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A selenium-doped sulfide solid electrolyte, characterized in that: Its chemical formula is Li 6±i P 1-x M x S 5-y Se y X, wherein 0≤i<1, 0<x<1, 0<y<1, M is one or more of Zr, Ta, Nb, Mo, Bi, In, Y, and X is one or more of Cl, Br, and F.
2. The selenium-doped sulfide solid electrolyte according to claim 1, characterized in that: Where 0≤i≤0.8, 0.01≤x≤0.8, 0.01≤y≤0.8; M is Zr and / or Nb.
3. The selenium-doped sulfide solid electrolyte according to claim 1, characterized in that: Where 0≤i≤0.5, 0.01≤x≤0.5, 0.01≤y≤0.5; M is Nb; X is Cl.
4. The selenium-doped sulfide solid electrolyte according to claim 1, characterized in that: The room temperature ionic conductivity of the sulfide solid electrolyte is 3×10 -3 ~5×10 -2 S / cm; And / or, after the sulfide solid electrolyte is exposed to a dry room dew point temperature of -40°C for 60 minutes, the room temperature ionic conductivity retention rate is ≥85%; And / or, after the sulfide solid electrolyte is immersed in a benzene organic solvent, an ester organic solvent, an ether organic solvent, acetonitrile or tetrahydrofuran for 30 minutes, the room temperature ionic conductivity retention rate is ≥80%; And / or, a symmetrical battery is assembled with metallic lithium as a symmetrical electrode and the sulfide solid electrolyte as an electrolyte layer. The symmetrical battery is cycle tested using a Blue Power CT2001A battery test system. The battery is measured at a current density of 0.1 mAcm -2 The lower stable cycle is ≥4000 hours.
5. The method for preparing a selenium-doped sulfide solid electrolyte according to claim 1, characterized in that: The following steps are involved: (1) According to the general formula Li 6±i P 1-x M x S 5-y Se y X, weigh Li2S, P2S5, LiX, selenium source and metal M source in stoichiometric ratios respectively and physically mix them to obtain precursor powder; (2) The precursor powder is calcined and naturally cooled to room temperature to obtain a selenium-doped sulfide solid electrolyte.
6. The preparation method according to claim 5, characterized in that: The selenium source and metal M source are Se powder, P powder and M a A b ; Or, the selenium source and the metal M source are M c Se d ; Among them, M is one or more of Zr, Ta, Nb, Mo, Bi, In, and Y, A is one or more of S, Cl, Br, and F, a=1~2, b=2~5, c=1~2, and d=2~5.
7. The preparation method according to claim 6, characterized in that: M a A b One or more of ZrS2, ZrCl4, TaCl5, TaS2, NbCl5, NbS2, MoCl5, MoS2, Bi2S5, BiCl3, In2S3, and YCl3; M c Se d It is one or more of ZrSe2, Ta2Se5, Nb2Se5, Mo2Se5, Bi2Se5, In2Se3, and Y2Se3.
8. The preparation method according to claim 5, characterized in that: The physical mixing is mechanical mixing, including high-energy ball milling, mechanical stirring, mechanical shaking, grinding or roller milling, and the mixing time is 20 minutes to 48 hours.
9. The preparation method according to claim 5, characterized in that: The calcination treatment is carried out in an inert atmosphere, the heating rate is 1-5°C / min, the calcination temperature is 500-600°C, and the calcination time is 0.5-24 hours.
10. An all-solid-state lithium secondary battery, characterized in that: It comprises a positive electrode, a negative electrode and the selenium-doped sulfide solid electrolyte according to claim 1.
Citation Information
Patent Citations
Inorganic compounds with an argyrodite-type structure, their preparation methods and their use in electrochemical applications
CA3136069A1
High-stability inorganic sulfide solid electrolyte and preparation method thereof
CN113363569A
Argyrodite type sulfide solid electrolyte containing lithium halide coating layer and preparation of argyrodite type sulfide solid electrolyte
CN114267874A
Preparation method and application of sulfide solid electrolyte
CN114744287A
Molybdenum-doped argyrodite type sulfide electrolyte and preparation method thereof
CN114883642A
Cited By
Selenium-doped sulfide solid electrolyte and preparation method thereof
CN120497427A
Modified PEO-based composite solid electrolyte as well as preparation method and application thereof
CN121172235A